Joint channel estimation and data detection algorithms for MIMO-OFDM systems - Kyeong Jin Kim; Jiang Yue (Conference Record of the Thirty-Sixth Asilomar Conference on Signals, Systems and Computers, 2002, 2002)
We propose a new joint channel estimation and data detection algorithms for the MIMO-OFDM system. Considering a received signal introduced by propagation delay and a channel with multipath fading, we used the extended Kalman filter (EKF) for a delay/channel estimator. As a data detector we separately apply the QRD-M algorithm. By separating the data detector and the delay/channel estimator, we can efficiently detect and estimate the unknown parameters. Also, a new delay/channel estimator leads to a better data detection performance.